Differing Perspectives on Older Adult Caregiving. (July 2016) - Brank, Eve M.; Wylie, Lindsey E.
Informal older adult caregiving allows older adults to stay in their homes or live with loved ones, but decisions surrounding older adult care are fraught with complexities. Related research and case law suggest that an older adult's need for and refusal of help are important considerations; the current study is the first to examine these factors experimentally. Two samples (potential caregivers and care recipients) provided responses regarding anticipated emotions, caregiver abilities, and allocation of daily caregiving decision making based on a vignette portraying an older adult who had a high or low level of autonomy and who accepted or refused help. Study findings suggest differing views about caregiving; potential caregivers may not be as well prepared to take on caregiving as the potential care recipients anticipate and potential caregivers may allocate more decisional responsibility to older adults than the care recipients expect. Implications for older adult abuse are discussed.